SOSIALISASI PEMANFATAAN LIMBAH BUAH DAN SAYUR SEBAGAI SALAH SATU ALTERNATIF PESTISIDA NABATI (PADA SISWA/SISWI MAGANG DI UPT UIRA AGROFARM UIR) - Sisca Voulina; Ilma Satriana Dewi; Elinur Elinur; Mardaleni Mardaleni; Tati Maharani (LP2M STP Mataram, 2024)
The community service activities with the theme about socializing use of fruit and vegetable waste as an alternative to botanical pesticides (eco-enzyme) on apprentice students at UPT UIRA Agrofarm UIR. The aim of this activity is to introduce and increase understanding apprentice students about the benefits of fruit waste as vegetable pesticides (eco-enzymes). This activity was carried out at UPT UIRA Agrofarm UIR, Teropong street, Pekanbaru, Riau Province, in a face-to-face event delivering material related to theory and techniques application of eco-enzymes. The lecturer team provides material according to their respective fields of knowledge and expertise. The implementation date is July 2023. The activity was attended by apprentice students from several schools including SMKN Integrated Agriculture Riau Province, SMKN 1 Rimba Melintang, SMKN 2 Rambah, and SMKN 1 Batang Gangsal Pertanian. Service activities that have been carried out and well received by apprentice students at UPT UIRA Agrofarm. Activity participants understood the material and practices that had been delivered with a percentage of 21.9% is really understood; understand 59.4%; and quite understand 18.8%. Then, regarding the usefulness of this service activity for participants, it was categorized as very useful (65.6%); useful (31.3%) and quite useful (3.1%).